Optimum sizing of the inverter for maximizing the energy yield in state-of-the-art high-concentrator photovoltaic systems. (1st September 2018) - Pérez-Higueras, Pedro J.; Almonacid, Florencia M.; Rodrigo, Pedro M.; Fernández, Eduardo F.
Highlights: Optimum sizing of the inverter in HCPV systems for maximizing the energy yield. One typical HCPV module, three types of inverters and four locations are analysed. Optimum sizing between 84% and 112% of the rated capacity of the generator is found. Sizing between 80% and 150% influences the Performance Ratio less than 1%. Optimum sizing increases with annual DNI and decreases with inverter efficiency. Abstract: The sizing of the inverter in comparison to the rated capacity of the photovoltaic generator is investigated for high-concentrator photovoltaic (HCPV) systems. An HCPV module of typical characteristics is modelled and parameterized, taking into account direct normal irradiance (DNI), ambient temperature, air mass and aerosol optical depth as atmospheric inputs, while the DC losses of the HCPV generator are allowed to vary in the ranges reported in the literature. A set of 80 commercial inverters are analysed to obtain the typical efficiency curves of state-of-the-art low-, medium-, and high-efficiency inverters. Four locations worldwide with high annual DNI levels and different average values of the weather variables influencing HCPV performance are studied. Results show that the inverter can be sized between 84% and 112% of the rated capacity of the HCPV generator at Concentrator Standard Test Conditions depending on the scenario considered for maximizing the final energy yield of the system. The proposed methodology uses analytical equations, all the model parameters are provided and justified and atmospheric inputs are obtained from meteorological databases in order to make the application easy regarding its use in other locations where the climate data is available.